Kontribusi Peer Social Support terhadap Career Decision Making Self-Efficacy pada Siswa SMAN Agam Cendekia - Zahrahnabila, Zahrahnabila; Dwatra, Free Dirga (Lembaga Yasin AlSys, 2024)
This study aims to determine this study aims to determine the contribution of peer social support to career decision making self-efficacy in students of SMAN Agam Cendekia. This study used quantitative methods. The population in this study were students of SMAN Agam Cendekia with sampling technique using proportionate stratified random sampling. The sample in this study was 138 people. The instruments used in this study are the career decision making self-efficacy CDMSE-SF and peer social support scale. The results of the analysis using a simple linear regression with significance of p=0.000 (p<0.05), correlation (R) of 0.297 and the value of the determinant coefficient (R square) of 0.88. This means that peer social support has a significant positive relationship with career decision making self-efficacy with a contribution of 8.8%.